Отражение языка художественной литературы в толковом словаре среднего объема - Bazarov, Evgenii (Wiener Slawistischer Almanach, 2023)
The article considers some features of and problems in the description in a medium-sized explanatory Russian dictionary of words used with metaphorical meanings in the language of fiction. In the first instance, a medium-sized explanatory dictionary should describe the active vocabulary of modern Russian; however, it should also in some measure reflect the lexical richness accumulated over the centuries which constitutes “passive” lexical knowledge. There are no clear criteria for determining the extent to which a medium-sized explanatory dictionary should reflect such “passive” vocabulary, including metaphorical word usage which is, obviously, frequently found in the language of fiction. The article compares and critically analyzes the material in two explanatory dictionaries – Dictionary of the Russian Language edited by A. P. Evgen′eva (1981–1984) and Academic Explanatory Dictionary of the Russian Language (2016). On the basis of the analysis of the material in these dictionaries, the author tries to elaborate guidelines for the representation of lexical units used metaphorically in the language of fiction. In the future, these recommendations could be used by lexicographers when compiling explanatory dictionaries.